2020
DOI: 10.2106/jbjs.20.00078
|View full text |Cite
|
Sign up to set email alerts
|

Hip Muscle Forces and Contact Loading During Squatting After Cam-Type FAI Surgery

Abstract: Background: Corrective hip surgery for cam-type femoroacetabular impingement (FAI) aims to improve hip function and prevent joint degeneration. The purpose was to compare muscle and hip contact forces (HCF) during squatting in cam-FAI patients before and after hip corrective surgery, and in healthy control participants (CTRL).Methods: Ten symptomatic cam-FAI male patients performed deep squatting pre-and at 2 years postoperatively. Patients were age, and body-mass-index matched to 10 CTRL male participants. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 65 publications
3
14
3
Order By: Relevance
“…Compared with CTRL individuals, lower magnitude HCF in those with symptomatic FAI has already been reported during gait (Ng et al, 2018b;Catelli et al, 2019b) and squat (Catelli et al, 2020). Our results showed that the ACM individuals also show significantly higher posterior HCF during both phases of the squat (descent and ascent) compared with their symptomatic peers, and resembling CTRL outputs.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Compared with CTRL individuals, lower magnitude HCF in those with symptomatic FAI has already been reported during gait (Ng et al, 2018b;Catelli et al, 2019b) and squat (Catelli et al, 2020). Our results showed that the ACM individuals also show significantly higher posterior HCF during both phases of the squat (descent and ascent) compared with their symptomatic peers, and resembling CTRL outputs.…”
Section: Discussionsupporting
confidence: 76%
“…It is hypothesized that the ACM kinematics, kinetics, and muscle forces outputs will resemble the CTRL levels, instead of the FAI. However, based on analysis of different tasks (Ng et al, 2018b;Catelli et al, 2019bCatelli et al, , 2020Catelli et al, , 2021, we expect the CTRL will still produce higher HCF compared to the other groups.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…While a plethora of literature on the relationship between HJCF and movements, such as walking, running, and stair climbing exist (Heller et al, 2001 ; Bergmann et al, 2004 ; Lenaerts et al, 2008 ; Giarmatzis et al, 2015 , 2017 ; Wesseling et al, 2015 ; Meyer et al, 2018 ; Kainz et al, 2020 ), only sporadic research has been done regarding other activities, such as single-leg standing or cycling (Bergmann et al, 2001 ; Varady et al, 2015 ; Damm et al, 2017 ) and even less that have dealt with specific hip-strengthening exercises. Catelli et al ( 2020 ) compared HJCFs during a squat between patients with the cam-type femoroacetabular impingement for both pre- and post-hip-corrective surgeries and with those of a healthy control in which they found no significant difference. In vivo measurements via instrumented endoprosthesis showed that only weight-bearing exercises caused significantly high HJCF (up to 441% of the body weight), whereas most of the others, such as non-weight-bearing, isometric exercises, did not (Schwachmeyer et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%